To Define and Inform : an Analysis of Information Provided in Dictionaries Used by Learners of English in China and Denmark. - Rasmussen, Saihong Li (Cambridge Scholars Pub., 2010)
""To Inform and Define: An Analysis of Information Provided in Dictionaries Used by Learners of English in China and Denmark"" presents a masterly synthesis of lexicographical theory in relation to bilingual and learner's dictionaries and advances a radical argument about how such dictionaries are used and how they should be improved for the convenience of students. By tracing the history of the terms 'semantic' and 'pragmatic' in linguistics and philosophy, Saihong Li shows the weakness of an ...